The Subject’s Guide to the Realms of Karma: Notes on Reading the Work of Dharma Master Taixu - Vrhovski, Jan (Buddhist Studies Review, 2023)
This article analyses the work of the Dharma Master Taixu, one of the leading figures of Chinese Buddhism in the Republican Period. Its analysis focuses on the meaning of concepts such as “human life,” “freedom,” and “karma” in Taixu’s seminal writings on the role of Buddhism in modern society, politics, and science from the 1920s and early 1930s. The succession of reading notes and reflections on these quintessential concepts in Taixu’s works aims at shedding some light on the relationship between subject and object, and the key question of the autonomy of the subject in modern Chinese Buddhism. Finally, by trying to illuminate the content of the ideas of subject and freedom in the work of this key figure, whose work is a foundational building block in the modernization of Buddhism in East Asia, the present discussion aims at casting some new light on the origins and theoretical foundations of contemporary Buddhism in Taiwan as well as in the broader Chinese cultural sphere.